Rancang Bangun Miniatur Plant Pusat Simulator Pompa Air Kotor Menggunakan Panel Kontrol Relay Kontaktor - Susilo; Sukamdi; Agus Andrianto; Heri Sungkowo; Dimas Eriyanto; Milzam Brillian Santana (Politeknik Negeri Malang, 2024)
Water pumps play an important role in the management of wastewater, particularly in maintaining environmental cleanliness and health. This research aims to design and create a miniature plant simulator for wastewater pumps using a relay contactor control panel. This miniature plant is designed to simulate the operation of the wastewater pump system automatically, replacing the often inefficient manual methods. The research process begins by determining the main components needed, such as a three-phase induction motor, contactors, thermal overload relays, and related sensors. Subsequently, the design and construction of the simulator and its control panel are carried out. Implementation includes testing the functionality of each component and the integrity of the overall system, including individual component testing and testing under system failure conditions. The research results show that the miniature plant simulator built functions well as expected. The automatic control system using relay contactors has proven effective in operating the water pump efficiently and safely. This miniature plant can be used not only as a learning tool but also as a prototype for developing larger and more complex wastewater pump control systems